Effect of Type 2 Diabetes Mellitus and Hypertension on Quality of Life: A Cross-Sectional Study - Goel, Simran; Anupam, Sristi; Bhatti, Karun; Mehta, Dinesh Kumar; Das, Rina (Scripta Medica, 2025)
Background/Aim: The quality of life (QOL) of the person is shown to be severely impacted by conditions such as type 2 diabetes mellitus (T2DM) and hypertension. Aim of this study was to investigate how both these conditions affect QOL of patients dealing with those conditions. Methods: A total of 276 participants were divided into three groups: T2DM (45.00 %), hypertension (14.75 %) and both conditions (40.25 %). The analysis included monitoring blood pressure and blood sugar levels. Participants completed a health quality evaluation questionnaire and data were expressed as mean ± standard deviation. Results: The results indicated that the duration of these diseases significantly impacted individuals' health. Physically, women were more adversely affected (12 %) than men (9.2 %) across all groups. Additionally, participants with mixed diets and both conditions experienced more negative effects (10.86 %) compared to vegetarians (6.25 %). It was found that individuals with T2DM and hypertension concurrently had a considerably lower QOL compared to those without these conditions. Conclusions: The study highlights that the type of diet and the duration of the disease significantly influence the QOL of patients. These factors were found to have a substantial impact on the overall well-being of individuals with T2DM and hypertension.